2023
DOI: 10.3390/ijerph20043071
|View full text |Cite
|
Sign up to set email alerts
|

The Dermatologic Care Needs of a Rural Community in South Florida

Abstract: For patients in rural areas, primary care is often their only access to healthcare services, and skin concerns are among the most common diseases seen in these settings. This study aims to investigate the most common skin conditions, management trends and patterns of referral to dermatology in a rural and underserved community in South Florida. A retrospective chart review was conducted using medical records from the C.L. Brumback Primary Care Clinic in Belle Glade, FL. The most common skin conditions were fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Another limitation for patients is the lack of access to a dermatologist. Access to a dermatologist is difficult to obtain for patients, such as those in rural areas, and there are non-compliance issues due to the distance from the nearest dermatologist [ 12 ]. Primary care physicians (PCPs) could potentially use IL5-FU areas where access is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation for patients is the lack of access to a dermatologist. Access to a dermatologist is difficult to obtain for patients, such as those in rural areas, and there are non-compliance issues due to the distance from the nearest dermatologist [ 12 ]. Primary care physicians (PCPs) could potentially use IL5-FU areas where access is limited.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, one retrospective review of medical records from a rural primary care clinic in Florida found that visits regarding skin cancer concerns were some of the most common dermatology-related encounters [ 16 ]. However, only 20% of patients were documented as having followed-up on their subsequent referral to a dermatologist.…”
Section: Nmscmentioning
confidence: 99%
“…Farmers are also exposed to pesticides during mixing, loading of pesticides, and when cleaning equipment and disposing of empty containers. Other activities associated with exposure include planting pesticidetreated seeds, weeding, and harvesting previously sprayed crops [6,7,8,9]. In the first decades of pesticides use, the main problem was the risk of acute intoxication among people who were occupationally exposed.…”
Section: Introductionmentioning
confidence: 99%
“…In the first decades of pesticides use, the main problem was the risk of acute intoxication among people who were occupationally exposed. But nowadays, the problem of diseases not directly related to the toxic potential of pesticides, most of which are non-toxic dermatoses, is gaining more and more interest [6,7,8,9]. Most of the dermatoses associated with pesticide application are contact dermatitis, both allergic and irritant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation